Clinical characteristics and changing trajectories of esophageal cancer and gastric cancer in China from 2010 to 2019: An analysis of a hospital-based database of 24,327 patients - Wang, Qiang; Zhang, Xiaorui; Zhong, Yuxin; Wei, Shijing; Li, Li; Wei, Wenqiang; Liu, Fen; Li, Yong; Wang, Shaoming (Frontiers in Oncology, 2023)
Purpose: This analysis aimed to investigate the clinical characteristics and changing trajectories of gastric cancer (GC) and esophageal cancer (EC). Methods: We collected data from a large cancer hospital in Beijing, China from 2010 to 2019. Joinpoint regression was used to analyze the trends of histological characteristics and comorbidity. Results: From 2010 to 2019, there were a total of 10 083 EC patients and 14 244 GC patients. Patients were mainly male, and diagnosed at 55-64 years old. Metabolic comorbidity was the most common comorbidity, with hypertension predominated. The percentages of stage I showed significant increases for EC (AAPC: 10.5%) and GC (AAPC: 9.7%) patients. We also observed an increasing trend of EC and GC patients over 65 years old. For EC patients, esophageal squamous cell carcinoma (93.1%) remained as the prioritized subtype and middle third of oesophagus was the most common site. EC patients with three or more comorbidities increased from 0.1% to 2.2% (AAPC, 27.7%; 95% CI, 14.7% to 42.2%). For GC patients, adenocarcinoma accounts for 86.9% of the total cases, and cardia was the most common site. Ulcerative comorbidity rate decreased from 2.0% to 1.2% (AAPC, -6.1%; 95% CI, -11.6% to -0.3%). Conclusion: ESCC remained as the prioritized histological subtype and middle third of esophagus was the most common site of EC. The majority of GC patients were adenocarcinoma, and cardia was the most common site. There was an increasing trend of patients diagnosed at stage I. These findings provide scientific evidence to guide future treatment.